2020
DOI: 10.1017/cjn.2020.87
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of MRI for Sensorineural Hearing Loss – An Audit

Abstract: Purpose: Contrast-enhanced magnetic resonance imaging (CEMRI) of the head is frequently employed in investigations of sensorineural hearing loss (SNHL). The yield of these studies is perceptibly low and seemingly at odds with the aims of wise resource allocation and risk reduction within the Canadian healthcare system. The purpose of our study was to audit the use and diagnostic yield of CEMRI for the clinical indication of SNHL in our institution and to identify characteristics that may be leveraged to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Two of the included studies did not include sino-nasal disease as an incidental finding (Hoekstra et al and Wong et al ), and two studies did not include multiple high signal white matter changes or small vessel disease as an incidental finding (Ahsan et al and Wong et al ). 1,9,20 A detailed breakdown of the results is shown in Table 2. A complete breakdown of all specific incidental findings is included in Table 1 in the supplementary material, and the conclusions of each included study are shown in Table 2 in the supplementary material, both available on The Journal of Laryngology & Otology website.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the included studies did not include sino-nasal disease as an incidental finding (Hoekstra et al and Wong et al ), and two studies did not include multiple high signal white matter changes or small vessel disease as an incidental finding (Ahsan et al and Wong et al ). 1,9,20 A detailed breakdown of the results is shown in Table 2. A complete breakdown of all specific incidental findings is included in Table 1 in the supplementary material, and the conclusions of each included study are shown in Table 2 in the supplementary material, both available on The Journal of Laryngology & Otology website.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic resonance imaging of the internal auditory meatus (MRI IAM) or the head enhanced with intravenous gadolinium administration has revolutionised the diagnosis of vestibular schwannoma. Magnetic resonance imaging of the IAM or the head has a sensitivity and specificity approaching 100 per cent 1 for the identification of this rare but potentially life-threatening condition. As such, this imaging technique is now considered the ‘gold standard’ for the diagnosis of vestibular schwannoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te functional network of the human brain is a complex and real network between a random network and a regular network, and its small-world attributes can ensure that the brain can efciently integrate and separate information under relatively low energy consumption [23]. Tis study found that at all thresholds, the fMRI parameters C p and L p of the patient group were dramatically superior to those of the control group.…”
Section: Discussionmentioning
confidence: 98%